Down-regulation of miR-125b by HPV16 E6 might promote cervical cancer progression through TAZ/TEAD - Hou, Yongli; Zhang, Lili; Wang, Wenhao; Cheng, Keyan; Wang, Hui; Ji, Yanfei; Su, Xiaoqiang; Hao, Min (Frontiers in Oncology, 2025)
BackgroundAbnormal gene expression due to the dysregulation of microRNAs (miRNAs) often occurred in the initiation or progression of cancers. In this attempt, we investigate whether miR-125b regulates biological behaviors of cervical cancer caused by HPV16 through TAZ.MethodsThrough the application of bioinformatics analysis techniques, differentially expressed miRNAs relevant to cervical cancer were identified. Cervical tissue specimens were collected from 15 patients with HPV16-positive cervical squamous cell carcinoma (stages IA-IIA), 15 patients with high-grade squamous intraepithelial lesion (HSIL), and 10 patients experiencing chronic cervical inflammation at the Second Hospital of Shanxi Medical University between May 2022 and May 2023. The quantitative assessment of miR-125b expression was conducted via real-time quantitative reverse transcription PCR(RT-qPCR). The potential regulatory relationship between miR-125b and TAZ was assessed using a dual-luciferase reporter assay. Within cervical squamous cell carcinoma SiHa cells, models were established using miR-125b mimic and inhibitor constructs to scrutinize cellular physiological processes and assess the expression profiles of miR-125b, TAZ, TEAD, and E6. Additionally, an HPV16 E6 overexpression cellular model was generated, and the expression patterns of miR-125b and its downstream targets were analyzed by RT-qPCR.ResultsTissue validation corroborated these findings, demonstrating a significant reduction in miR-125b expression levels in HSIL and cervical squamous cell carcinoma compared to normal cervical tissue (P < 0.05). Functional assays using a miR-125b mimic revealed inhibited proliferation, migration, and invasion of SiHa cells along with enhanced apoptosis, concomitant with decreased expression of HPV16 E6, TAZ, and TEAD mRNA. Conversely, these effects were reversed upon introduction of a miR-125b inhibitor. Notably, overexpression of HPV16 E6 was associated with suppressed miR-125b expression (P < 0.05) and enhanced TAZ and TEAD expression (P < 0.05), as corroborated by western blot analysis.ConclusionHPV E6 promotes the malignant progression of cervical cancer cells by downregulating miR-125b, which targets TAZ, thus regulating the Hippo pathway. Consequently, miR-125b emerges as a promising therapeutic target for HPV-induced cervical cancer.